A 1.7–2.7-GHz 4-bit Phase shifter based on packaged RF MEMS switches. Issue 5 (23rd March 2016) - Huang, Yulin; Li, Xinyi; Bao, Jingfu; Deng, Di; Wang, Yiling; Du, Yijia
Abstract : This study presents a 4-bit phase shifter with a maximum phase shift degree of 75° based on packaged metal-contact single-pole double-throw (SPDT) radio frequency microelectromechanical system (RF MEMS) switches mounted on a 20 mil RO4350 substrate and assembled with its driver module on a 4-layer printed circuit board (PCB) board. Electric length of 10° and characteristic impedance of 61.7 Ω are selected for T-stub matching. Standard PCB processing makes it easy to develop and suitable for taking place of mechanical tilt employed in recent base station. Measurements indicate a maximum insertion loss of 1.37 dB at 2.7 GHz and a minimum return loss of 11.71 dB. The phase accuracy is within 1.75° at 2.7 GHz.